Towards an integrated framework for sustainability: evaluating selected projects from Saudi Arabia - Selim, Haitham Sadek; Abuzaid, Abdullah (Frontiers in Built Environment, 2024)
The capital of Saudi Arabia is evolving into one of the most attractive cities in the Middle East due to various ambitious expansion projects aligned with Vision 2030. This urban development strategy requires researchers to adopt evaluation approaches based on comprehensive sustainability criteria, including environmental and cultural sustainability, community involvement, and economic feasibility. This study utilizes the Delphi methodology to define evaluation criteria and their importance, employing the Delphi technique to gather insights from a group of experts through three rounds of questionnaires. The responses were analyzed using the Top-of-Priority Similarity to Ideal Solution (TOPSIS) technique to develop an integrated evaluation model, which assessed architectural practices in Riyadh through three key projects: The King Fahad National Library, Qasr Al-Hokm, and Saudi Arabia's Digital City. Data sources included extensive site visits, project documentation, and expert evaluations. The evaluation model demonstrated varying levels of sustainability across the projects. The King Fahad National Library and Qasr Al-Hokm showed high scores in sustainability practices, while Digital City lagged behind in several areas, highlighting the need for improvement. This research enhances the understanding of how globalization influences urban renewal in Riyadh and emphasizes the importance of developing effective evaluation models that address the multifaceted nature of sustainability. The findings underscore the need for continuous reassessment of architectural initiatives in the city to align with both international standards and local cultural contexts. The proposed evaluation model successfully tests sustainability frameworks at the local level, indicating areas for future enhancements and contributing valuable insights toward achieving sustainable urban development in Saudi Arabia.